Knowledge on Complementary Feeding Among Mothers of Under Two Years Children in Surkhet - Chhetri, Poonam Khadka; Basnet, Sandhya; Thapa, Sangita (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Complementary Feeding is important at the first two years of life because it is crucial for higher cognitive function development, language acquisition, the formation of sensory pathways for vision and hearing, and brain development. The aim of the study was to assess the level of knowledge on complementary feeding among mothers of under two years of children in a hospital. Method: A Descriptive- Cross sectional study was conducted among 97 mothers of under two years children in a Karnali Province Hospital in a Surkhet using a non- probability purposive sampling technique. Ethical approval was taken from Institutional Review Committee (IRC) of MMIHS. Informed consent was obtained prior to data collection. Data was collected through face to face interview by using a self-developed structured interview schedule then analyzed and interpreted by descriptive and inferential statistics through SPSS version 2023. Results: More than half (52.6%) have adequate knowledge on complementary feeding. Almost all (96.6%) of the respondents answered correctly regarding meaning of complementary feeding. Almost all (92.8%) of the respondent answered breastfeeding continue up to 24 months. However inadequate knowledge present on frequency of feeding of 6 to 9 month age child (46.4%) and amount of feeding for 9-12 months age child (44.3%) and only (36.1%) of respondent answered seasonal fruits should be given once a day. There was a statistically significant association between level of knowledge on complementary feeding with ANC Visits of the respondents (p=0.002). Conclusion: The findings of the study conclude that more than half of the respondents had an adequate knowledge on complementary feeding among mothers. Despite of this there is inadequate knowledge on amount and feeding of food according to age. This indicates need of awareness program.